Detection of Protein Cd2ap in Mice (Mus Musculus) Kidney Damage Induced by 4% NaCl - Lia Septya; Ahmad Ridwan (Biotropic : The Journal of Tropical Biology, 2024)
CD2-associated protein (CD2AP) is a podocyte protein and its presence in urine is consistent with changes in renal function index. Indications of proteinuria often characterized by Focal Segmental Glomerulosclerosis (FSGS). Purpose: To detect CD2AP as an early indicator and determine CD2AP concentration against the stages of kidney damage through three main parameters, quantification of urine CD2AP and serum creatinine confirmed by histopathology. The study involved 24 male mice divided into three Control and three Treatment Groups (4% NaCl induction) for two, four and six weeks. Quantitative analysis was carried out to determine the concentration of CD2AP using ELISA in urine and creatinine levels in serum using the Jaffe method followed by FSGS as qualitative analysis. Results: There were significant differences of CD2AP concentration between each treatment and control group (P≤0,05), whereas each treatment group showed differences but not significant (P≥0,05). The control and treatment group serum creatinine did not show a significant difference (P≥0,05). Kidney histopathology displays FSGS to indications of global sclerosis at the 4th-week and 6th-week treatment group. Conclusions: The presence of CD2AP in urine can be used as an early indicator of kidney damage but can not show a significant difference at each stage of kidney damage.